Notch signalling and the initiation of neural development in the Drosophila eye. - Baonza, A.; Freeman, M. (Development, 2001)
Neural determination in the Drosophila eye occurs progressively. A diffusible signal, Dpp, causes undetermined cells first to adopt a 'pre-proneural' state in which they are primed to start differentiating. A second signal is required to trigger the activation of the transcription factor Atonal, which causes the cells to initiate overt photoreceptor neurone differentiation. Both Dpp and the second signal are dependent on Hedgehog (Hh) signalling. Previous work has shown that the Notch signalling pathway also has a proneural role in the eye (as well as a later, opposite function when it restricts the number of cells becoming photoreceptors - a process of lateral inhibition). It is not clear how the early proneural role of Notch integrates with the other signalling pathways involved. We provide evidence that Notch activation by its ligand Delta is the second Hh-dependent signal required for neural determination. Notch activity normally only triggers Atonal expression in cells that have adopted the pre-proneural state induced by Dpp. We also report that Notch drives the transition from pre-proneural to proneural by downregulating two repressors of Atonal: Hairy and Extramacrochaetae.